MLP and RBF Symbol Tracking with 16 QAM Modulation Over Multipath Distorted Channel - Bouguerra, Fateh; Benacer, Imad; Saidi, Lamir (International Conference on Advanced Systems and Electric Technologies (IC_ASET), 2017)
Multilayer Perceptron (MLP) and Radial Basis Function (RBF) were proposed in this paper as two models of non-linear ANN based equalization techniques in order to optimize processing performance, tracking, and minimize error of the channel effects and the ascending noise with 16 QAM Modulation, this work will be referenced with one of the most used linear adaptive equalization; Recursive least squares (RLS), as an evaluation. The two models will be compared in terms of efficiency and robustness facing noisy channel.